Genome-wide characterization of aldehyde dehydrogenase gene family members in groundnut (Arachis hypogaea) and the analysis under saline-alkali stress - Zhang, Xiaoming; Zhong, Jingwen; Cao, Liang; Ren, Chunyuan; Yu, Gaobo; Gu, Yanhua; Ruan, Jingwen; Zhao, Siqi; Wang, Lei; Ru, Haishun; Cheng, Lili; Wang, Qi; et al. (Frontiers in Plant Science, 2023)
Groundnut or peanut (Arachis hypogaea) is a legume crop. Its seeds are rich in protein and oil. Aldehyde dehydrogenase (ALDH, EC: 1.2.1.3) is an important enzyme involved in detoxification of aldehyde and cellular reactive oxygen species, as well as in attenuation of lipid peroxidation-meditated cellular toxicity under stress conditions. However, few studies have been identified and analyzed about ALDH members in Arachis hypogaea. In the present study, 71 members of the ALDH superfamily (AhALDH) were identified using the reference genome obtained from the Phytozome database. A systematic analysis of the evolutionary relationship, motif, gene structure, cis-acting elements, collinearity, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and expression patterns was conducted to understand the structure and function of AhALDHs. AhALDHs exhibited tissue-specific expression, and quantitative real-time PCR identified significant differences in the expression levels of AhALDH members under saline-alkali stress. The results revealed that some AhALDHs members could be involved in response to abiotic stress. Our findings on AhALDHs provide insights for further study.